Microsecond pulse generation in an actively q-switched all-pm fiber laser based on an electro-optic modulator - Fadhel, Mahmoud Muhanad; Razali, Muda; Hamzah, Abdulwahhab Essa; Norazida, Ali; Mohd Saiful, Dzulkefly Zan; Norhana, Arsad (Institute of Electrical and Electronics Engineers Inc, 2022)
Active Q-switching of an all polarizationmaintaining (All-PM) erbium fiber laser by an electro-optic modulator (EOM) is reported. Cavity loss modulation is achieved via an external modulation signal generated from an electrical signal source. The Q-switched pulsed laser operates in the 1.5μ m region with 0.83 nm linewidth. The shortest pulse width obtained is 1.06μ s. We believe that this combination between all-PM configuration and EOM offers an ideal method to design single-polarization pulsed laser sources with high environmental stability towards temperature variations and mechanical perturbations.